2012
DOI: 10.1155/2012/854539
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Behavior of Human Dentin under Uniaxial Compression

Abstract: Deformation behavior of a human dentin under compression including size and rate effects is studied. No difference between mechanical properties of crown and root dentin is found. It is mechanically isotropic high elastic and strong hard tissue, which demonstrates considerable plasticity and ability to suppress a crack growth. Mechanical properties of dentin depend on a shape of samples and a deformation rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…However, the plastic deformation is active channel of stress accommodation in human dentin independently from the orientation of dentin channels [15,16]. The difference in deformation behavior of these hard tissues is caused by the considerable distinction in amount of organics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the plastic deformation is active channel of stress accommodation in human dentin independently from the orientation of dentin channels [15,16]. The difference in deformation behavior of these hard tissues is caused by the considerable distinction in amount of organics.…”
Section: Resultsmentioning
confidence: 99%
“…Macroscopic schemes of deformation, which give information on the properties of whole material, such as compression and tension (diametral compression) do not allow revealing the strong dependence of the mechanical properties of enamel from the orientation of enamel rods [10][11][12][13][14]. Non-uniformed arrangement of enamel rods in the volume of sample can be the cause of this experimental fact, as it take place in human dentin under the same testing condition [15,16]. Modeling of the deformation behavior of enamel, also suggests that the direction along the enamel rods is most rigid [17].…”
Section: Introductionmentioning
confidence: 99%
“…Samples with a high aspect ratio behave like rubber, while samples with a low aspect ratio exhibit an almost brittle response. No size effect has been observed in human dentin [1,2].…”
Section: Introductionmentioning
confidence: 89%
“…No preferred orientation of the dentin channels was observed in the samples, because the size of the samples was comparable with the size of the crowns. It has also been shown that this parameter does not affect the mechanical properties of dentin under compression [1].…”
Section: Methodsmentioning
confidence: 99%
“…Еще раньше при испы-таниях на релаксацию напряжений [20] было показано, что модуль релаксации дентина линейно зависит от логарифма времени в течение примерно четырех деся-тилетий, и что распределение времен релаксации для выбранной ориентации образцов в значительной степени постоянно в течение этого периода времени. Недав-нее систематическое экспериментальное исследование in vitro [21][22][23] деформационного поведения дентина при сжатии с учетом влияния размера и формы образцов, а также скорости нагружения, показало, что его механиче-ские свойства существенно зависят от этих параметров, что, в частности, объясняется авторами пластичностью органической составляющей дентина, представленной КВ, и пористостью межтрубочкового дентина. Эти экс-перименты также подтвердили представление о дентине как о вязкоупругом материале, способном выдерживать большие упругие и значительные необратимые дефор-мации, а также эффективно сопротивляться развитию трещин [24].…”
Section: Introductionunclassified